THE INFLUENCE OF THE CELEBRAM ON INTEREST IN BUYING THE MONSTA X ALBUM WITH TRUST AS AN INTERVENING VARIABLE ON MONBEBE IN MEDAN CITY - Arda, Mutia; Ayu Pratiwi, Widya (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The purpose of this research is to find out and analyze the influence of Celebgram on Buying Interest, to find out and analyze Selebgram on Trust, to find out and analyze Trust and Buying Interest, to find out and analyze the influence of Selebgram on Buying Interest through Trust in Monbebe (Monsta X fans) in Medan. The approach used in this study is an associative approach. The associative approach is an approach that uses two or more variables to determine the relationship or influence between one variable and another. The population in this study were fans of Monsta X in Medan, amounting to 100 people. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses Path Analysis, Partial Least Square (PLS) and Hypothesis Testing. Data processing in this study using the SmartsPLS 3. 0 software programs. From the results of the study, it is known that there is a significant relationship between celebgrams on buying interest, celebgrams on trust, trust in buying interest and there is a significant indirect relationship between celebgrams on buying interest through trust in buying Monsta X albums at Monbebe in Medan